High Energy High Protein Enteral Nutrition from Soybean and Cowpea for Tuberculosis Patients - Yuni Prisilia Sihotang; Yenny Moviana; Surmita; Mona Fitria (Jurusan Gizi Poltekkes Kemenkes Bandung, 2026)
Tuberculosis is a directly transmitted infectious disease caused by Mycobacterium tuberculosis. Patients with tuberculosis (TB) are at risk of experiencing a decline in nutritional status if not supported by an appropriate dietary intake. Nutritional requirements can be met through the administration of enteral nutrition. Enteral Soyvia is a high-energy, high-protein alternative enteral food product formulated from soybeans (Glycine max) and cowpeas (Vigna unguiculata). This study aimed to evaluate the effect of varying formulations of soybean and cowpea flour on the organoleptic properties, total energy, macronutrient content (protein, fat, and carbohydrates), flow rate, and osmolality of the product. An experimental design was employed using three formulations: F1 (40% soybean flour: 60% cowpea flour), F2 (50%:50%), and F3 (60%:40%). Organoleptic properties were assessed through hedonic testing involving 30 semi-trained panelists. The results indicated that the F2 formulation had the most favorable organoleptic characteristics, with an overall acceptance score of 5.57. The Kruskal–Wallis test showed that differences in soybean and cowpea flour ratios significantly affected taste (p = 0.006) and consistency (p = 0.023). Nutritional analysis revealed that all formulations met the energy and carbohydrate requirements for enteral nutrition and qualified as high-protein; however, the fat content did not meet standard enteral nutrition criteria. The flow rate of Enteral Soyvia F1 met the tolerance standards for bolus administration of enteral formulas. However, the osmolality of all formulations exceeded the recommended limits for enteral products. The production cost per serving of Enteral Soyvia was economical, estimated at approximately 36% of the market price of commercial high-energy, high-protein enteral formulas. Further research is recommended to enhance the formulation by incorporating additional ingredients to meet all nutritional standards for enteral food products.